MULTIMEDIA INTERAKTIF EDUKASI LIMBAH SAMPAH DAN CARA PENGELOLAANNYA MENJADI BARANG KERAJINAN TANGAN - Saryoko, Andi (www.bsi.ac.id, 2018)
Learning media is a tool used to convey learning materials as well as a tool to stimulate thoughts, feelings, attention and interest to learn. As in the case of waste knowledge, the fact is that some people are still unable to understand the types of waste and how to use them into useful handicrafts. This is because some of the information media is still less clear and detailed in the delivery of information about garbage so that the community is difficult to understand. This is one of the factors that cause the decreasing of public interest in processing waste waste into handicraft items. Limitations of this means that encourage authors to design interactive educational media-based educational information along with interesting visual illustrations and easy to understand about everything about waste and its management into handicrafts with value for use. The purpose of the interactive animation design created by the author is to help the community to more easily understand about waste, impact and how to make it into handicraft goods through interactive multimedia, attract people to learn more in developing creative ideas making handicrafts made from waste waste and as an alternative to learning the manufacture of handicrafts in addition to using the article media. Keywords: Interactive Animation, Trash, Crafts